Staphylococcus aureus sensitivity and resistance profile. Experience at Hipolito Unanue National Hospital - Mamani, Edgardo (2006)
Objective: The determine Staphylococcus aureus susceptibility to different antimicrobians in both inpatients and outpatients. Design: Retrospective analysis. Setting: Hipolito Unanue National Hospital, a teaching hospital. Materials: From January through December 2003 we determined sensitivity and resistance of Staphylococcus aureus strains obtained from the respiratory tract. Interventions: We used the Kirby - Bauer method in the Bacto Mueller Hinton Medium following the CLSI recommendations. Main outcome measures: Sensitivity to antibiotics. Results: Two hundred and seventeen Staphylococcus aureus strains originated from the respiratory tract were isolated. Oxacillin resistance in inpatiens was found in 32% of strains, to gentamicin 35%, and to ciprofloxacin 58%, and 100% sensitivity to vancomycin. Conclusion: Low resistance to oxacillin was found.